Performance of granular activated carbon to remove micropollutants from municipal wastewater—A meta-analysis of pilot- and large-scale studies. (October 2017) - Benstoem, Frank; Nahrstedt, Andreas; Boehler, Marc; Knopp, Gregor; Montag, David; Siegrist, Hansruedi; Pinnekamp, Johannes
Abstract: For reducing organic micropollutants (MP) in municipal wastewater effluents, granular activated carbon (GAC) has been tested in various studies. We did systematic literature research and found 44 studies dealing with the adsorption of MPs (carbamazepine, diclofenac, sulfamethoxazole) from municipal wastewater on GAC in pilot- and large-scale plants. Within our meta-analysis we plot the bed volumes (BV [m 3 water /m 3 GAC ]) until the breakthrough criterion of MP-BV20% was reached, dependent on potential relevant parameters (empty bed contact time EBCT, influent DOC DOC0 and manufacturing method). Moreover, we performed statistical tests (ANOVAs) to check the results for significance. Single adsorbers operating time differs i.e. by 2500% until breakthrough of diclofenac-BV20% was reached (800–20, 000 BV). There was still elimination of the "very well/well" adsorbable MPs such as carbamazepine and diclofenac even when the equilibrium of DOC had already been reached. No strong statistical significance of EBCT and DOC0 on MP-BV20% could be found due to lack of data and the high heterogeneity of the studies using GAC of different qualities. In further studies, adsorbers should be operated ≫20, 000 BV for exact calculation of breakthrough curves, and the following parameters should be recorded: selected MPs; DOC0; UVA254 ; EBCT; product name, manufacturing method and raw material of GAC; suspended solids (TSS); backwash interval; backwash program and pressure drop within adsorber. Based on our investigations we generally recommend using reactivated GAC to reduce the environmental impact and to carry out tests on pilot scale to collect reliable data for process design. Graphical abstract: Highlights: Adsorbers operating time differs by 2500% until diclofenac-BV20% was reached. Elimination of diclofenac even when equilibrium of DOC was reached. No strong statistical significance of EBCT and DOC0 on MP-BV20% due to lack of data and high heterogeneity of studies. Adsorbers should be operated ≫20, 000 BV for exact calculation of breakthrough curves. We generally recommend using reactivated GAC and to carry out pilot tests.